2022
DOI: 10.3390/medicina58101336
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship between Voice Quality and Obstructive Sleep Apnea Severity and Cumulative Percentage of Time Spent at Saturations below Ninety Percent: Voice Analysis in Obstructive Sleep Apnea Patients

Abstract: Background and Objectives: Apnea hypopnea index is the most important criterion in determining the severity of obstructive sleep apnea (OSA), while the percentage of the total number of times which oxygen saturation is measured below 90% during polysomnography (CT90%) is important in determining the severity of hypoxemia. As hypoxemia increases, inflammation will also increase in OSA. Inflammation in the respiratory tract may affect phonation. We aimed to determine the effects of the degree of OSA and CT90% on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Later, Robb et al ( 27 ) reported that OSA speakers exhibited lower formant values and wider formant bandwidths compared to the non-OSA speakers, and they attributed this alteration to the longer vocal tract length and excessive vocal tract tissue compliance in patients with OSA. A recent study ( 28 ) explored the relationship between voice quality and OSA severity; according to its voice analysis results, there were significant differences between OSA and non-OSA individuals in the fundamental frequency, jitter percentage, shimmer percentage, harmonic-noise ratio (HNR), and maximum phonation times as the severity of OSA increased.…”
Section: Speech and Osamentioning
confidence: 99%
“…Later, Robb et al ( 27 ) reported that OSA speakers exhibited lower formant values and wider formant bandwidths compared to the non-OSA speakers, and they attributed this alteration to the longer vocal tract length and excessive vocal tract tissue compliance in patients with OSA. A recent study ( 28 ) explored the relationship between voice quality and OSA severity; according to its voice analysis results, there were significant differences between OSA and non-OSA individuals in the fundamental frequency, jitter percentage, shimmer percentage, harmonic-noise ratio (HNR), and maximum phonation times as the severity of OSA increased.…”
Section: Speech and Osamentioning
confidence: 99%